2014
DOI: 10.28945/1986
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Combining Algorithm and Program Animation: A Case Study with Data Structure Course

Abstract: Data Structure is an important and mandatory course in Computer Science and Information Technology curricula. The topics of the course require detailed view of the algorithm behavior with the implementation part by a programming language. This paper introduces a visualized learning environment and assesses the effectiveness of using this system in order to enhance the education in computer science and information technology concerning data structure course. Whether the use of the system will produce remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Several studies have examined the impact of using visualizations in learning data structures. Some of the few works which are closely related to our works are those of the authors in [28][29][30]. The authors in [28] conducted an experimental study to compare the effect of using text-based instructional materials, interactive software visualization, or their combination on learning data structures.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the impact of using visualizations in learning data structures. Some of the few works which are closely related to our works are those of the authors in [28][29][30]. The authors in [28] conducted an experimental study to compare the effect of using text-based instructional materials, interactive software visualization, or their combination on learning data structures.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [29] studied the impact of using a PV tool called Courseware in learning data structures. Results showed that students who used the Courseware outperformed those who used the traditional lecture approach.…”
Section: Related Workmentioning
confidence: 99%
“…Others suggested animated models for teaching aspects of computer systems organization (Henderson, 1994). Researchers have analyzed the effectiveness of combining algorithm and program animation with data structure in courses (Osman & Elmusharaf, 2014). Some researchers directed analysis for using instructional animation, and reported significant benefit over the use of static elements (Hoffler & Leutner, 2007).…”
Section: Litreture Reviewmentioning
confidence: 99%